2015
DOI: 10.1039/c4ra14676j
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches to understanding reaction outcomes of organic processes in ionic liquids

Abstract: The utility of using a combined experimental and computational approach for understanding ionic liquid media, and their effect on reaction outcome, is highlighted through a number of case studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 290 publications
(470 reference statements)
0
28
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17] Varying the charge distribution within each ion, while keeping a ±1 e charge on each ion, can significantly affect dynamic properties. For example, Li and Kobrak compared MD simulations using octahedral ions with either a symmetric (charge spread equally over the ion) or non-symmetric (charge localised on one half of the ion) charge distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17] Varying the charge distribution within each ion, while keeping a ±1 e charge on each ion, can significantly affect dynamic properties. For example, Li and Kobrak compared MD simulations using octahedral ions with either a symmetric (charge spread equally over the ion) or non-symmetric (charge localised on one half of the ion) charge distribution.…”
Section: Introductionmentioning
confidence: 99%
“…9 Multiple other MD studies have found that varying charge distribution can lead to 3 significant changes in predicted structural, dynamic or energetic properties. [10][11][12][13][14][15][16][17] Therefore, understanding the charge distribution within ILs is key to linking IL composition with macroscopic physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical and physical properties such as viscosity, polarity, hydrophobicity, and Lewis acidity and basicity can be adjusted by judicious combination of a cationic and an anionic component in the IL. These unique features of ILs have potentially been exploited in various elds of analytical chemistry, 2-4 electrochemistry, [5][6][7] synthesis and catalysis, [8][9][10] and materials chemistry. [11][12][13] In particular, several reviews have investigated extensively water-immiscible hydrophobic ILs composed of a bis(triuoromethanesulfonyl)imide (Tf 2 N À ) anion as extraction media in liquid-liquid distribution (LLD).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, polarizability depends on the structure of ionic liquids matrices as shown in Figure 4. Quantum chemical calculations for imidazolium-based room temperature ionic liquids showed that the polarizability is isotropic dipolar polarizability or anisotropic dipolar polarizabilities [19]. Polarizability of the two series is different for the two series ( Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The values depend on the solvent properties and their interactions [21]. It has been reported that polarizability of RTILs reduce viscosity and increase ionic diffusion [19,[22][23][24].…”
Section: Resultsmentioning
confidence: 99%